2022
DOI: 10.1002/tox.23459
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester induces radiosensitization via inhibition of DNA damage repair in androgen‐independent prostate cancer cells

Abstract: In the present study, we evaluated the radiomodulatory potential of caffeic acid phenethyl ester (CAPE), an active component of traditional herbal medicine propolis. CAPE has been identified as a potent anticancer agent in multiple cancer types and is reported to have the dual role of radioprotection and radiosensitization. However, the radiomodulatory potential of CAPE in prostate cancer (PCa), which eventually becomes radioresistant is not known. Therefore, we studied the effect of cotreatment of CAPE and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Therapeutic effects of propolis on numerous diseases, such as infections, hypertension, cardiovascular disorders, diabetes, allergies, asthma, and cancer, are assigned to its anti-oxidative, immuno-modulatory, and anti-inflammatory properties [ 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 88 ]. These diseases are accompanied by mitochondrial dysfunction and increased ROS production and the enzymatic and non-enzymatic oxidation of polyunsaturated fatty acids (PUFAs).…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
See 2 more Smart Citations
“…Therapeutic effects of propolis on numerous diseases, such as infections, hypertension, cardiovascular disorders, diabetes, allergies, asthma, and cancer, are assigned to its anti-oxidative, immuno-modulatory, and anti-inflammatory properties [ 3 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 88 ]. These diseases are accompanied by mitochondrial dysfunction and increased ROS production and the enzymatic and non-enzymatic oxidation of polyunsaturated fatty acids (PUFAs).…”
Section: Molecular and Cellular Targets Of Propolis And Its Flavonoid...mentioning
confidence: 99%
“…Many lines of evidence suggest that immunomodulation by propolis and its polyphenolic/flavonoid components is an important contributing factor to the antitumor and antimetastatic activities of these compounds. Flavonoids may induce the immune system [ 3 , 16 , 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 92 , 214 , 215 , 216 , 217 , 218 , 220 , 221 , 222 , 223 ], and act as powerful free radical scavengers [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 39 , 40 , 41 , 42 , 58 , 63 ]. Accordingly, a high dietary intake of flavonoids from propolis is associated with a reduced risk of cancer at different anatomical sites [ 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Antitumor Activity Of Propolis and Its Polyphenolic/flavonoi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeic acid is moderately available in sunflower seeds, applesauce, apricots, and prunes. Caffeic acid phenethyl ester (CAPE), a central component of propolis, has also been investigated for its chemo-sensitizing [ 51 , 52 ] and radio-sensitizing [ 53 ] effects against various types of cancer. The radio-sensitizing effect of this substance was evaluated in 2005 by Chen, et al [ 49 ] against CT26 colorectal adenocarcinoma cells and in vivo on BALB/c mice implanted with these cells.…”
Section: Dietary Phenolic Compounds Improving the Chemosensitivity Of...mentioning
confidence: 99%
“…These authors noted, in vitro, an improvement in the destruction of CT26 cells by ionizing radiation (IR) and, in vivo, an extension of animal survival and a marked inhibition of tumor growth compared to radiotherapy alone. The mechanism of action explaining this radio-sensitivity was elucidated very recently on prostate cancer cells (DU145 and PC3) by co-treatment using gamma radiation (GR) and CAPE [ 53 ]. Results showed that this combined treatment sensitizes the cells to radiotherapy by reducing the RAD50 and RAD51 proteins and the cell migration potential, mainly by inhibiting DNA damage repair.…”
Section: Dietary Phenolic Compounds Improving the Chemosensitivity Of...mentioning
confidence: 99%